PENDEKATAN ANTROPOLOGI DALAM PENDIDIKAN ISLAMUNTUK MERAWAT KEMAJEMUKAN - Siregar, Mustamar Iqbal (Department of Anthropology, 2018)
This paper discusses the use of anthropological approaches in Islamic education. In this process, there is a serious effort to integrate and interconnect the two sciences while seeing how far the positive implications are for reformulating the curriculum and the learning process. So that the texture that will be seen from Islamic education is more multicultural. And normatively, Islamic teachings are no longer presented in their textual-partial, radical forms, but are more substantial-contextual. The final projection of methodological creations based on literature review is the emergence of Islamic education as commander for efforts to care for the plurality of the nation in Indonesia. So that the nature of universality and elasticity of Islam is very felt, both among its followers, as well as for allhumanity.